2005
DOI: 10.1016/j.jvs.2005.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Increased growth rate of abdominal aortic aneurysms in women, the Tromso Study

Abstract: Conclusion:A computer-based program to alert physicians regarding the use of venous thromboembolism (VTE) prophylaxis markedly reduced rates of pulmonary embolism and deep venous thrombosis (DVT) in hospitalized patients at risk for VTE.Summary: The authors hypothesized that use of a computer alert program to alert physicians regarding hospitalized patients at high risk for VTE might reduce the frequency of DVT by increasing the frequency of prophylaxis. A computer program was developed linked to a patient dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
43
0
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(50 citation statements)
references
References 0 publications
4
43
0
3
Order By: Relevance
“…Solberg found that over a five year period, the mean growth rate of aneurysms amongst men was 1.82mm/year in contrast to 2.43mm/year in women (Solberg 2005, Mofidi 2007. This is consistent with the finding o f the…”
Section: Gendersupporting
confidence: 85%
“…Solberg found that over a five year period, the mean growth rate of aneurysms amongst men was 1.82mm/year in contrast to 2.43mm/year in women (Solberg 2005, Mofidi 2007. This is consistent with the finding o f the…”
Section: Gendersupporting
confidence: 85%
“…22 Although a single small study suggested that female gender was an independent predictor of growth rate, the magnitude of the difference was only 0.7 mm per annum. 23 For a given diameter, the time to rupture is less in women than in men. 24 In the UK Small Aneurysm Trial, the risk of rupture in women was 4-fold that of men (hazard ratio, 4.0; 95% CI, 2.0 to 7.9).…”
mentioning
confidence: 99%
“…Scott and colleagues conducted the only RCT (Chichester trial) which studied the value of screening in women over the age of 65 in an unselected population (n=9342) 21 . They reported the prevalence of AAA in women to be 1·3 percent, with other authors reporting a similar rate of 0·7-1·3 percent in unselected populations [22][23][24] . Scott et al did not demonstrate a difference in rupture rates between the women randomized to screening and control populations of women at 5-and 10-year follow-up 21 .…”
Section: Targeted Screening For Aaamentioning
confidence: 72%